Penerapan Metode Simple Queue dalam manajemen Bandwith Jaringan Komputer Local Area Network (LAN) Pada PT. Uni Gemilang Sentosa Jakarta: Jaringan Komputer Local Area Network (LAN) - Septyani, Herlina; Noviriandini, Astrid; Indriyani, Luthfi (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2024)
The Internet is a familiar part of business, government education, industry, and even offices, as at PT. Uni Gemilang Sentosa. Network system problems at PT. Ulni Gelmilang Selntosa is the absence of bandwidth management, which regulates the speed of the Internet for the Internet, so that the speed of the Internet is unstable between one and the other, which causes the use of the Internet not to be optimal, especially if someone is carrying out uploads and downloads. Bandwidth management controls and measures communications (network traffic and packets) on a network link to avoid congestion and poor performance. Simple queue is a method for limiting bandwidth by dividing bandwidth from small to medium and managing each user's upload and download bandwidth. One solution for bandwidth to be used more optimally is having bandwidth management using the simple queue method available on the network using MikroTik with bandwidth management at PT. Uni Gemilang internet access becomes smooth between one user and another according to their respective capacities.